Política de Educação Especial em tempos de pandemia da COVID-19 (2020) - Alves, Suelen Priscila Ferreira (Universidade Federal de São Carlos, 2022)
During 2020, with the recommendations of social isolation, Emergency Remote Teaching was accepted as a possibility for the continuity of the school year. In this direction, the Federal Government, Ministry of Education and the National Council of Education and Private Institutions released documents to guide and provide educational guidelines for this period. Focusing on Special Education policies in Brazil, this research has the general objective of analyzing Special Education policies in Brazil in the face of changes justified by the COVID-19 (2020) pandemic. And specific objectives: a. To analyze the social, political and economic context of Brazil in times of the COVID-19 pandemic; B. Characterize the proposed changes to special education in the investigated period; C. Expose the arguments for formulating consensus presented by groups that dispute Special Education policies in Brazil. Given this reality, the main question of this research is: what are the proposed changes to the Special Education policy, justified by the validity of the COVID-19 pandemic? This research supported by Dialectic Historical Materialism has document analysis as its methodological procedure. Data collection was carried out on the website of the Ministries of Education, National Council of Education, Todos Pela Educação and Instituto Rodrigo Mendes. The official documents were saved in folders and the drill down was described in a Word document. The Iramuteq software was used to support data processing. A discourse analysis was carried out through the category of Integral State from Antonio Gramsci. The following documents were analyzed: Opinion CNE/CP nº 5/2020; Opinion CNE/CP No. 11/2020; Opinion CNE/CP No. 15/2020; Opinion CNE/CP No. 16/2020; Decree No. 10,502; Protocols on inclusive education during the COVID-19 pandemic: an overflight through 23 countries and international organizations; Technical note: the return to face-to-face classes in the context of the COVID-19 pandemic; Technical note: distance learning in basic education in the face of the COVID-19 pandemic. The results of the analysis point to the expansion of the possibilities of privatization of Special Education, expansion of Distance Education, involvement of private hegemony devices and companies in the formulation of policies, proposal for training teachers for socio-emotional skills and hybrid teaching, proposal for reduced education activities and far from a perspective of humanization, expansion of school inequality and exclusion of students with disabilities. The results showed that the policies proposed for Special Education in this period of 2020, this pandemic, do not innovate in relation to what was already proposed, however, it deepens historical relationships in the area such as the privatization and segregation of students served by this policy. Conditions that point to the need to fight for public schools.
Special Education policy in times of the COVID-19 pandemic (2020)
Keywords: Educação Especial; Pandemia; Políticas Públicas em Educação; Special Education; Pandemic; Public Policies in Education; CIENCIAS HUMANAS::EDUCACAO